Reciprocity and the tragedies of maintaining and providing the commons - Gaechter, Simon; Kölle, Felix; Quercia, Simone (Nature Publishing Group, 2017)
Social cooperation often requires collectively beneficial but individually costly restraint to maintain a public good, or it needs costly generosity to create one. Status quo effects predict that maintaining a public good is easier than providing a new one. Here, we show experimentally and with simulations that even under identical incentives, low levels of cooperation (the ‘tragedy of the commons’) are systematically more likely in maintenance than provision. Across three series of experiments, we find that strong and weak positive reciprocity, known to be fundamental tendencies underpinning human cooperation, are substantially diminished under maintenance compared with provision. As we show in a fourth experiment, the opposite holds for negative reciprocity (‘punishment’). Our findings suggest that incentives to avoid the ‘tragedy of the commons’ need to contend with dilemma specific reciprocity.